Calcium Oxalate Induces Renal Injury through Calcium-Sensing Receptor - Li, Xiaoran (Oxid Med Cell Longev, 2016)
Objective. To investigate whether calcium-sensing receptor (CaSR) plays a role in calcium-oxalate-induced renal injury. Materials and Methods. HK-2 cells and rats were treated with calcium oxalate (CaOx) crystals with or without pretreatment with the CaSR-specific agonist gadolinium chloride (GdCl(3)) or the CaSR-specific antagonist NPS2390. Changes in oxidative stress (OS) in HK-2 cells and rat kidneys were assessed. In addition, CaSR, extracellular signal-regulated protein kinase (ERK), c-Jun N-terminal protein kinase (JNK), and p38 expression was determined. Further, crystal adhesion assay was performed in vitro, and the serum urea and creatinine levels and crystal deposition in the kidneys were also examined. Results. CaOx increased CaSR, ERK, JNK, and p38 protein expression and OS in vitro and in vivo. These deleterious changes were further enhanced upon pretreatment with the CaSR agonist GdCl(3) but were attenuated by the specific CaSR inhibitor NPS2390 compared with CaOx treatment alone. Pretreatment with GdCl(3) further increased in vitro and in vivo crystal adhesion and renal hypofunction. In contrast, pretreatment with NPS2390 decreased in vitro and in vivo crystal adhesion and renal hypofunction. Conclusions. CaOx-induced renal injury is related to CaSR-mediated OS and increased mitogen-activated protein kinase (MAPK) signaling, which subsequently leads to CaOx crystal adhesion.